Influence of Internal Factors and External Factors on Non Performing Financing in Islamic Commercial Banks - Alfakhirah, Nadirah Nur; Jaya, Tiara Juliana (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2024)
This study aims to see the effect of the variables Return on Assets (ROA), Capital Adequacy Ratio (CAR), Operating Costs and Operating Income (OCOI), Financing to Deposit Ratio (FDR), inflation and Gross Domestic Product (GDP) on Non-Performing Financing (NPF) for Islamic commercial  banks in Indonesia for the 2018-2022 period. This type of research uses quantitative research methods. The analytical tool used is multiple linear regression analysis using E-views version 10 software. The sample in this study is Islamic Commercial Banks in Indonesia. The results showed that simultaneously the variables ROA, CAR, OCOI and FDR had a significant effect on Non-Performing Financing (NPF), while simultaneously, the variables Inflation and GDP did not have a significant effect on Non-Performing Financing (NPF). Partially CAR, OCOI, and FDR have a significant effect on Non-Performing Financing (NPF), whereas ROA, Inflation and GDP have no effect on Non-Performing Financing (NPF). Internal factor variables have an effect of 88.2% on Non-Performing Financing (NPF), while 11.8% are influenced by other variables not examined. External factor variables have an effect of 3.1% on Non-Performing Financing (NPF), while 96.9% are influenced by other variables not examined.